Analisis Psikopatologi Kecenderungan Impulsive Buying pada Salah Satu Mahasiswa Universitas Negeri Semarang (Jurnal Ilmiah Psikologi MIND SET, 2021)
Impulsive buying can have a negative impact on individuals. Based on the preliminary study, the respondent stated that one of the negative impacts arising from the tendency of impulsive buying was financial problems, which led to a feeling of discomfort that did not match the criteria of mental health. This study aims to determine the tendency of impulsive buying among students in terms of psychopathology. The respondent in this study is one of the Semarang State University students who has a tendency to impulsive buying. The data in this study were obtained from semi-structured interviews and were analyzed using holistic analysis. The data credibility test is done by using the member check technique. The results of the study refer to the tendency of impulsive buying to respondents which can be caused by psychoanalytic aspects (intrapsychic conflict of respondents when they are 4 years old), behavioral aspects (wrong learning patterns where respondents always see their parents who continue to provide what they ask for), and cognitive aspects ( mistakes in thinking, that the respondent thinks all desires must be properly satisfied).